An evolutionary game study on the cooperation behavior of the “government, banks, and guarantee institutions” in financing guarantee for China’s new agricultural entities - Zhang, Jingjing; Mei, Zhu; Zhang, Fan; Zhou, QiaoMei (Frontiers in Physics, 2023)
“Government, Bank and Guarantee Institution” cooperative financing guarantee (hereinafter referred to as the cooperation mechanism) is an important way to alleviate the financing difficulties of China’s new agricultural entities and raise the credit line of bank financing. In order to find out an effective way for the improvement of low-level equilibrium in the actual operation of the cooperation mechanism, this paper builds the three-party evolutionary game model relating to local government, bank and agricultural guarantee institute under incomplete information with all partners of the cooperation mechanism as the study object. This model focuses on the weak activeness, strong dependence, poor cooperation effect, lower credit line of guarantee and other specific problems. Moreover, this paper analyzes the equilibrium solution of this model, extracts the significant factors affecting the positive cooperation behaviors of the three parties (government, bank and guarantee institution) in the view of interest realization. Analog simulation is performed to explore the key conditions for truly alleviating the financing risks of new agricultural entities, thus helping improve the operation quality of the cooperation mechanism. According to the study results, the focus of “Government, Bank and Guarantee Institution” cooperation should be shifted from post risk sharing to prior risk identification. Specifically, the government should further share the high-quality information affiliated to farmland management rights and reflecting the status of risks, guide banks and agricultural guarantee institutions to share the cost of risk identification, accelerate the acquisition of higher information transformation value and prevent the “free rider problem”. In the last part, policies are recommended in four aspects, including risk information sharing, risk identification quality improvement, risk identification cost sharing and risk information value transformation, which are of practical guiding significance for the sustainable development of “Government, Bank and Guarantee Institution” financing guarantee for China’s new agricultural entities.